Control de calidad en obra para hormigones de alto desempeño - Garnica Enderica, Napoleón (2009)
One of the biggest challenges for concrete’s technology is to increase the useful life in service of the structure. The technological development, experimentation and analysis based on the observation, allowed to increase the use spectrum and application from the special concretes to that now is denominated High Performance Concrete, HPC. The quick deterioration of reinforced concrete structures has a direct relationship with the environment, materials, technical norms and control procedures. In the HPC these phenomenon are presented with more intensity due to their physical, chemical, mechanical characteristic matters, and the defects become evident. The useful life of a structure depends on its durability. It’s possible to deduce that it is in the construction phase where is feasible that more errors could be made whose effects on the structure will have a major impact due to the not controlled environment that occur in the field to obtain the same results of a Laboratory. Because of this fact, becomes notorious the necessity to complete and to apply consciously all specifications, regulations and quality systems to control and monitoring the several phases that get involved during the execution of the project.